Maternal and perinatal health in developing countries [ - Hussein, Julia; McCaw-Binns, Affette; Webber, Roger (CABI, 2012)
The promotion of maternal health and mortality reduction is of worldwide importance, and constitutes a vital part of the UN Millennium Development Goals. The highest maternal mortality rates are in developing countries, where global and regional initiatves are needed to improve the systems and practices involved in maternal care and medical access. Taking a practical policy approach, this book covers the background and concepts underlying efforts to improve maternal and perinatal mortality, the current global situation and problems that prevent progress.